2014
DOI: 10.7790/ajtde.v2n3.55
|View full text |Cite
|
Sign up to set email alerts
|

The importance of circumstance: Digital access and affordability for people experiencing homelessness

Abstract: Summary:Access to and affordability of digital technology for vulnerable and disadvantaged groups is an ongoing concern in an Australian context, however the digital needs, issues and barriers for consumers who are homeless are largely neglected in this literature. This paper presents findings from a research project on mobile phones and the internet in the lives of people experiencing homelessness and engages with some key issues of digital exclusion arising in the context of a general shift in connectivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Wider concerns around digital exclusion and broader ethical concerns have been emphasised elsewhere, 22 , 53 including in the Ada Lovelace Institute rapid review, 21 but are not currently well quantified. Some populations that are particularly vulnerable to the health impacts of COVID-19 (eg, older adults, people who are homeless, and socioeconomically deprived populations) are also less likely to own a smartphone, 17 , 22 , 54 , 55 potentially amplifying their risks because contact-tracing apps could—for similar reasons—be less likely to reduce transmission within their social circles. 33 Such challenges are more acute in low-income countries than in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Wider concerns around digital exclusion and broader ethical concerns have been emphasised elsewhere, 22 , 53 including in the Ada Lovelace Institute rapid review, 21 but are not currently well quantified. Some populations that are particularly vulnerable to the health impacts of COVID-19 (eg, older adults, people who are homeless, and socioeconomically deprived populations) are also less likely to own a smartphone, 17 , 22 , 54 , 55 potentially amplifying their risks because contact-tracing apps could—for similar reasons—be less likely to reduce transmission within their social circles. 33 Such challenges are more acute in low-income countries than in high-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…For populations in state care, the contacts as currency theme indicates how broad social networks with shallow ties with peers beyond state care may be sought and orientated. Similarly, this theme converges and builds upon the trends emergent from previous research (Ellison et al, 2010;Guadagno et al, 2013;Humphry, 2014).…”
Section: Theme 1 -Contacts As Currencymentioning
confidence: 53%
“…Given that tailored cessation support offered through internet‐based resources has been found to improve the likelihood of successful quit attempts among the general population, 27 this option may represent an underused alternative that could be the focus of future interventions. Access to technology is not necessarily a major barrier, as Australians experiencing homelessness have high rates of mobile phone use and approximately three‐quarters have access to a smartphone; however, data charges may be a possible barrier to use if public Wi‐Fi hotspots are unavailable 28 . Given the lack of research on utilisation of online cessation resources by people experiencing disadvantage, future research could invite members of these groups to assist in the design of online resources to ensure they are acceptable and appropriate for addressing their specific needs.…”
Section: Discussionmentioning
confidence: 99%
“…Access to technology is not necessarily a major barrier, as Australians experiencing homelessness have high rates of mobile phone use and approximately three-quarters have access to a smartphone; however, data charges may be a possible barrier to use if public Wi-Fi hotspots are unavailable. 28 Given the lack of research on utilisation of online cessation resources by people experiencing disadvantage, future research could invite members of these groups to assist in the design of online resources to ensure they are acceptable and appropriate for addressing their specific needs. For example, in the present study, online resources were not identified by interviewees as providing emotional support during quit attempts, so future online interventions may include features to address this concern.…”
Section: Discussionmentioning
confidence: 99%